Factors that influence care for second and third trimester termination of pregnancy for medical reasons in Canada: A qualitative investigation - Madeleine Ennis; Elise Lavoie-Lebel; Regina Renner; Sarah Munro; Carmelina Barone; Elana Ilott; Jennifer Chisholm; Brigid Dineley; Liv Knutzen; Julie Robertson; Jessica Liauw (PLoS ONE, 2026)
Background Termination of pregnancy in the 2 nd /3 rd trimester for medical reasons is an essential health service. Our objective was to explore the factors that influence 2 nd /3 rd trimester abortion care for medical reasons in Canada from the perspective of healthcare providers. Methods We conducted one-on-one, semi-structured interviews with healthcare providers across the 10 Canadian academic maternal fetal medicine (MFM) centres. The interviews were conducted in English or French, and we collected participant demographic information through an online survey. We used reflexive thematic analysis to identify healthcare providers’ perspectives of barriers and facilitators that impact care for 2 nd /3 rd trimester abortion for medical reasons at their centres. Our analysis was informed by a realist standpoint. We used NVivo14 Software to organize our analysis. Findings We recruited 28 participants – 10 MFM specialists, 9 medical geneticists/genetic counsellors, and 9 nurses/social workers. We identified six main themes describing factors that influence termination care: 1) Provider commitment amid burnout and discomfort regarding abortion care; 2) Provider availability and team structure ; 3) Logistical factors that support coordinated and compassionate care, including the availability of a dedicated care coordinator, are instrumental to how care is delivered; 4) Advantages and challenges of local guidelines highlights a tension between desiring structured equitable guidelines and facilitating flexibility to tailor care to meet individual needs; 5) Considerations for patient equity by adjusting care based on patients’ lived experiences; 6) Communicating with and supporting patients emphasizes the importance of patient-centered communication and opportunities to help patients navigate their grief and bereavement. Conclusions Healthcare providers identified key factors that promote or hinder 2 nd /3 rd trimester abortion care for medical reasons in Canada. Understanding which barriers to address and facilitators to amplify will inform efforts to optimize equitable, patient-centred, supportive, and comprehensive healthcare services.